Pelaksanaan Perjanjian Kerja Waktu Tertentu Terhadap Pekerja PT BTU - Muhammad Azwar AM (Pusat Riset dan Inovasi Nasional, 2024)
Competition for jobs makes workers accept jobs without having to pay attention to the employment relationship system, so that in the future contract workers do not receive legal certainty. Contract workers, hereinafter referred to as fixed-term work agreements (PKWT), in their implementation give rise to multiple interpretations which tend to be violated by employers. The case example that I took occurred at PT BTU which incidentally employed its employees for 5 to 7 years continuously without paying attention to the labor regulations that apply in Indonesia. The research method used in this research is a normative legal research method, which aims to explain the aspects studied in a complete, detailed, clear and systematic manner in legislation. This research uses a statutory approach, where the research process is carried out by examining all laws and regulations related to the legal issue being researched. From the research results, it can be proven that PT BTU violates labor regulations in Indonesia.